Combined Neurotoxic Effects of Commercial Formulations of Pyrethroid (Deltamethrin) and Neonicotinoid (Imidacloprid) Pesticides on Adult Zebrafish (Danio rerio): Behavioral, Molecular, and Histopathological Analysis - Adriana Petrovici; Gheorghe Savuța; Carla Lucini; Madalina-Andreea Robea; Carmen Solcan (Life)
The use of different commercial products that involve one or multiple active substances with specific targeted-pests control has become a widespread practice. Because of this, a severe range of significant consequences has been often reported. Among the most used pesticides worldwide are deltamethrin (DM) and imidacloprid (IMI). With a significative effect on the insect’s nervous system, DM acts on the voltage-gated sodium channels in nerve cell membranes, while IMI mimics the acetylcholine neurotransmitter by binding irreversibly to the nicotinic acetylcholine receptors. This study investigates the neurotoxic effects of sub-chronic exposure to commercial formulations of deltamethrin (DM) and imidacloprid (IMI) in adult zebrafish, both individually and in combination. The formulations used in this study contain additional ingredients commonly found in commercial pesticide products, which may contribute to overall toxicity. Fish were exposed to environmentally relevant concentrations of these pesticides for 21 days, individually or in combination. Behavioral, molecular, and histopathological analyses were conducted to assess the impact of these pesticides. Zebrafish exhibited dose-dependent behavioral alterations, particularly in the combined exposure groups, including increased erratic swimming and anxiety-like behavior. Gene expression analysis revealed significant changes in neurotrophic factors (BDNF, NGF, ntf-3, ntf-4/5, ntf-6/7) and their receptors (ntrk1, ntrk2a, ntrk2b, ntrk3a, ntrk3b, ngfra, ngfrb), indicating potential neurotoxic effects. Histopathological examination confirmed neuronal degeneration, gliosis, and vacuolization, with more severe impairments observed in pesticide mixture treatments. These findings highlight the neurotoxic potential of pesticide formulations in aquatic environments and emphasize the need for stricter regulations on pesticide mixtures and further research on pesticide interactions. Our findings emphasize that the combination of pesticides could trigger a synergistic effect by maximizing the toxicity of each compound. Thus, it is a well-known practice for pyrethroids and neonicotinoids to be used together in agriculture. Even so, its prevalence in agriculture and the need to investigate its actual impact on human health, biodiversity, and ecosystem mitigates the development of new strategies for assessing the risk and, at the same time, enhancing the effectiveness.